Lintel of the doorway of the sanctum - Temples of India Project Team (Jio Institute, 2024)
The lintel of the doorway of the sanctum. At the lalata is a figure of Lakulisha. The frame is richly carved with musicians and dancers. The current lintel on the doorframe of the Harshnath temple is likely a later replacement. This lintel, depicting Lakulisha, may have belonged to the Harshnath Temple.